1969
DOI: 10.1002/jctb.5010190501
|View full text |Cite
|
Sign up to set email alerts
|

Formation and reactivity of borides, carbides and silicides. I. Review and introduction

Abstract: Borides, carbides and silicides are reviewed with special reference to newer production methods and fabrication techniques. Crystal structures and types of bonding in binary and ternary compounds are classified and discussed. The scope and limitations of the Pauling‐Rundle theory, molecular orbital treatment and the Ubbelohde‐Samsonov theory are examined critically and appropriate experimental evidence is summarised. Information so far available on the sintering of borides, carbides and silicides is summarised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 88 publications
1
3
0
2
Order By: Relevance
“…They also reported that M23C6 type carbides for W-Fe-C systems are metastable at these temperature ranges. This occasion has been confirmed by other studies as well [6,7]. In another study, Upadhyaya [8] investigated the formation kinetics of Fe-containing MC, M6C, and M12C carbides in metal matrix composites.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…They also reported that M23C6 type carbides for W-Fe-C systems are metastable at these temperature ranges. This occasion has been confirmed by other studies as well [6,7]. In another study, Upadhyaya [8] investigated the formation kinetics of Fe-containing MC, M6C, and M12C carbides in metal matrix composites.…”
Section: Introductionsupporting
confidence: 74%
“…This situation was confirmed by different studies. [6,7]. Hou, Linder [16], and C. B. Pollock [40] performance.…”
Section: Fe-based Binder Systemsmentioning
confidence: 99%
“…(Fig. 3c), les éléments Cr, Ni, Si, O et C ont été identifiés avec la possibilité de former des composés stables selon l'énergie libre de formation [18]. L'analyse EDS de la région 2 ( Fig.…”
Section: Caractérisation Mécanique Et Tribologiqueunclassified
“…D'autre part, le diborure de titane (TiB 2 ) peut être utilisé comme renfort pour les alliages autofondants à base de Ni, parce qu'ils présentent une dureté (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) GPa) et une température de fusion (3225°C) très élevées [7]. L'addition de TiB 2 aux revêtements de NiCrBSi doit donc améliorer leur résistance à l'usure.…”
Section: Introductionunclassified
“…14−17 These metalrich phosphides are noted for their hardness, strength, and high thermal and chemical stability, akin to traditional metallic compounds such as carbides, nitrides, borides, and silicides. 18 They also exhibit excellent thermal and electrical conductivity. Unlike carbides and nitrides, metal-rich phosphides showcase distinct structural characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%